2019
DOI: 10.3390/polym11050842
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrophobic Modification of Old Newspaper and Its Application in Paper Fiber Reinforced Composites

Abstract: Paper fibers have gained broad attention in natural fiber reinforced composites in recent years. The specific problem in preparing paper fiber reinforced composites is that paper fibers easily become flocculent after pulverization, which increases difficulties during melt-compounding with polymer matrix and results in non-uniform dispersion of paper fibers in the matrix. In this study, old newspaper (ONP) was treated with a low dosage of gaseous methyltrichlorosilane (MTCS) to solve the flocculation. The modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Nonetheless, in both cases, tensile strength was slightly decreased and elongation at break remained almost constant. Apparently, the maleic anhydride rings in MAPE should create hydrogen bonds between HDPE and the protein in BF, as in the case of glass or cellulosic fibers [ 39 , 40 ]. However, it becomes apparent that the rest of compounds present in the BF, such as ash or chrome oxides, limited these interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in both cases, tensile strength was slightly decreased and elongation at break remained almost constant. Apparently, the maleic anhydride rings in MAPE should create hydrogen bonds between HDPE and the protein in BF, as in the case of glass or cellulosic fibers [ 39 , 40 ]. However, it becomes apparent that the rest of compounds present in the BF, such as ash or chrome oxides, limited these interactions.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of the authors' knowledge, the impact strength of natural fiber-reinforced PP composites has been researched, obtaining notable results [7,11]. Nonetheless, the information on the impact strength of newspaper fiber-reinforced composites is scarce [29,30]. Thus, adding further results that stress the capabilities of a source of recycled fibers from waste has importance.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization rate of newspaper was further improved. Compared with the method of crushing newspapers for extrusion production [23], the flexural strength and tensile strength of the obtained materials had been increased by nearly 260% and 188%, respectively (the performance value under the optimal conditions of each process). It is shown that the use of the entire sheet of paper can help to improve some of the mechanical properties of the composite material.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are also many problems in the process, such as paper fiber tends to become flocculent after comminution, which increases the difficulty of melting and blending with the polymer matrix, and results in uneven dispersion of paper fiber in the matrix. Our research team has found that old newspaper can solve the flocculation problem with low-dose gaseous methyltrichlorosilane (MTCS) treatment [23]. Some scholars had also investigated the impact of deinking methods of waste newspapers on the properties of composite materials [24].…”
Section: Introductionmentioning
confidence: 99%